2023
DOI: 10.2169/internalmedicine.1314-22
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Synbiotics in Patients Undergoing Autologous Hematopoietic Stem Cell Transplantation: A Randomized, Double-blinded, Placebo-controlled Pilot Study

Abstract: Objective High-dose chemotherapy with autologous hematopoietic stem cell transplantation (auto-HSCT) is an effective treatment option for relapsed and refractory aggressive malignant lymphoma. However, patients frequently experience treatment-induced gastrointestinal symptoms. Synbiotics, including live microorganisms and nondigestible food ingredients, reportedly ameliorate chemotherapy-induced mucosal damage. In this study, we assessed the efficacy and safety of synbiotics in patients undergoing auto-HSCT. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…BEE of patients was calculated according to Harris-Benedict formula. The adjusted body weight of overweight patients with BMI > 24 kg/m 2 was calculated using the following formula (Mizutani et al, 2023 ): …”
Section: Methodsmentioning
confidence: 99%
“…BEE of patients was calculated according to Harris-Benedict formula. The adjusted body weight of overweight patients with BMI > 24 kg/m 2 was calculated using the following formula (Mizutani et al, 2023 ): …”
Section: Methodsmentioning
confidence: 99%
“…Synbiotics, a mixture of live microorganisms and substrate (s) selectively utilized by host microorganisms confers a health benefit on the host [84], and it reportedly ameliorates chemotherapy-induced mucosal damage. One RCT experiment demonstrated that the intake of Bifidobacterium longum (BB536) and guar gum significantly attenuated diarrhea and anorexia after engraftment, indicating that synbiotics attenuated gastrointestinal toxicity effects [85]. Although many studies have reported the beneficial effects of prebiotics and probiotics on bone marrow transplantation, the direct influence of prebiotics and probiotics on HSCs needs to be elucidated.…”
Section: Probiotics and Prebioticsmentioning
confidence: 99%